The Role of Product Innovation and Distribution Strategy in Enhancing Competitive Advantage in Export Markets - Wuranti, Hayu; Nurhayati, Siti (AKSIOMA : Jurnal Manajemen, 2026)
This study addresses a gap in the literature that remains limited in examining the simultaneous role of product innovation and distribution strategy in building competitive advantage, particularly in export-oriented manufacturing firms. This study aims to examine the effect of product innovation and distribution strategy on competitive advantage in export markets, with a case study of PT Boga Makmur Gracia. A quantitative approach was employed using primary data collected from 30 respondents selected through purposive sampling. Data were gathered using a structured questionnaire with a Likert scale and analyzed using multiple linear regression. The results indicate that product innovation and distribution strategy simultaneously have a significant effect on competitive advantage (F = 27.50; p < 0.001). Partially, product innovation has a positive and statistically significant effect (? = 0.215; t = 2.104; p < 0.05), although its contribution is relatively modest. In contrast, the distribution strategy demonstrates a stronger and more dominant positive effect (? = 0.541; t = 2.356; p < 0.05). Furthermore, the model explains 65.3% of the variance in competitive advantage (R² = 0.653). These findings suggest that while product innovation remains important as a source of differentiation, an effective distribution strategy plays a more critical role in enhancing competitive advantage in export markets. Therefore, firms are encouraged to integrate continuous product innovation with strengthened distribution networks and strategic logistics partnerships to achieve sustainable competitive advantage.